Donor-σ-acceptor molecules with alkyl σ-linkers of different lengths: Exploration on the exciplex emission and their use for efficient organic light-emitting diodes. (December 2022) - Song, Yongjun; Yu, Renyou; Meng, Xianwen; He, Lei
Abstract: Donor-σ-acceptor molecules featuring exciplex emission have been extensively researched for developing thermally-activated delayed fluorescence; however, varying the length of alkyl σ-linker to explore the exciplex emission and to develop efficient exciplex emitters has not been fully conducted. Herein, we report donor-σ-acceptor exciplex emitters (1–3 ) developed with 9, 9-dimethyl-10-phenyl-9, 10-dihydroacridine donor, 2, 4, 6-triphenyl-1, 3, 5-triazine acceptor, and alkyl σ-linkers of different lengths (−CH2 − for 1, –CH2 CH2 − for 2, and –CH2 CH2 CH2 − for 3 ). The chemical structures of 1 –3 have been verified by X -ray crystallography. Theoretical calculations reveal that intramolecular through-space charge transfer is the dominant charge-transfer mechanism within the molecules. In dilute solution and the films with low concentration of the dopant, intramolecular exciplexes are formed, whereas in the films with high concentration of the dopant, both intra- and inter-molecular exciplexes are formed. 1–3 all show aggregation-induced emission properties. In heavily doped or neat films, 1–3 show sky-blue emission with photoluminescent efficiency of up to 0.70 and high reverse intersystem crossing rates of up to 5.1 × 10 6  s −1 . It is shown that varying the length of alkyl σ-linker regulates the thermally-activated delayed fluorescence of the exciplex formed in neat film. Vacuum-evaporated and solution-processed organic light-emitting diodes using 1–3 as the emitters show sky-blue and blue electroluminescence with peak external quantum efficiencies of up to 14.5% and 13.0%, respectively. The efficiency is among the highest for solution-processed blue organic light-emitting diodes based on small-molecule exciplex emitters reported so far. Highlights: Donor-σ-acceptor emitters were prepared with alkyl σ-linkers. The length of the alkyl σ-linker was varied to tune the emission properties. The emitters showed high k risc of up to 5.1 × 10 6  s −1 in films. Solution-processed blue OLEDs using the emitters showed high EQEs of up to 13%.